2020
DOI: 10.1007/s11060-020-03467-y
|View full text |Cite
|
Sign up to set email alerts
|

High expression of estrogen receptor alpha and aromatase in glial tumor cells is associated with gender-independent survival benefits in glioblastoma patients

Abstract: Introduction Glioblastoma multiforme (GBM) is a highly malignant glial tumor, affecting men more often than women. The reason for this gender-specific predominance remains unclear, raising the question whether these effects are subject to hormonal control. The purpose of this study was to examine the expression of estrogen receptor alpha (ERα) and aromatase in human GBM tissue samples in relation to patient survival and furthermore to investigate the effect of standard chemotherapy in combination with estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…[ 42 ] In agreement with this, a recent study showed that estradiol (at high concentrations) decreased cell viability and increased sensitivity to TMZ. [ 43 ] Conversely, few in vitro studies have also shown the opposite effect of estradiol. At low concentrations, estradiol increased proliferation and mitochondrial fitness of U87 cells.…”
Section: Role Of Estrogen In Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…[ 42 ] In agreement with this, a recent study showed that estradiol (at high concentrations) decreased cell viability and increased sensitivity to TMZ. [ 43 ] Conversely, few in vitro studies have also shown the opposite effect of estradiol. At low concentrations, estradiol increased proliferation and mitochondrial fitness of U87 cells.…”
Section: Role Of Estrogen In Gliomamentioning
confidence: 99%
“…One study showed that ERα is absent in T98G, U87, LN229, U138, MO59J, MO59K;[ 48 ] whereas, other studies show that ERα is expressed in U373 and D54,[ 23 ] and also in LN229, LN18, U251, U87, T98G cell lines. [ 43 47 ] These differences may have arisen due to the technique/molecule (mRNA/protein) being tested and/or differences in antibodies used/passage number of the cells.…”
Section: Role Of Estrogen In Gliomamentioning
confidence: 99%
“…We may reasonably explain the latter finding with the fact that intratumoral estradiol concentrations down-regulate the expression of estrogen receptor-α in terms of mRNA and protein content as a classical biological feature of the occurred estrogen receptor-α wild type functional transactivation [ 33 , 34 ]. The data of Jiménez research work [ 13 ] appeared to not fit with those of Honikl and coworkers [ 35 ], who reported how in 60 glioblastoma patients, the increase of aromatase is concomitant with a longer survival even though the intratumoral estradiol concentrations are not documented. In addition, the latter study reported how the administration of estrogen at supraphysiological doses ranging from 10 to 50 µM dramatically reduced glioblastoma cell viability.…”
Section: Discussionmentioning
confidence: 88%
“…The higher incidence of gliomas in male patients when compared with their premenopausal female counterparts has been attributed to the protective effects of oestrogen. The discovery of oestrogen receptors and aromatase enzymes which converts testosterone to oestradiol in certain gliomas further supports the significant influence of sex hormones in tumour cell proliferation and death [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 98%